Assessing Lignin Decomposition and Soil Organic Carbon Contents Across a Tropical Savannah-Rainforest Boundary in Guyana - Black, Jasmine E.; Wagner, Thomas; Abbott, Geoffrey D. (Frontiers in Forests and Global Change, 2021)
The soils beneath the rainforest of Guyana have the potential to hold, and release, large stores of carbon under land use and climate change. Little is known about soil carbon stocks or molecular dynamics in this region. This study therefore aims to elucidate differences in the molecular (lignin and tannin) and bulk soil organic carbon (SOC) stocks in different ‘sub-environments’ along a rainforest-savannah boundary, setting a framework for further investigation into the soil carbon dynamics of the region. Bulk SOC analysis shows that Gleysols have the highest stocks, particularly those under rainforest vegetation (swamp and island forests surrounded by savannah), whereas Plinthosols have significantly lower SOC stocks. Texture and soil water content analysis indicates that predominantly clay soils play a role in high SOC stocks, whilst predominantly sandy soils prevent SOC stocks from accumulating. Clay and sand are present in both Gleysols and Plinthosols, to different extents. Analysis of lignin and tannin in surface soils of the sub-environments reveals clear differences in molecular composition. Heavily degraded lignin signatures in rainforest Gleysols suggests a surrounding physio-chemical environment which promotes their degradation. Conversely, Plinthosols beneath woodland within the savannah have the greatest amount of lignin and tannin products. The presence of the clay mineral kaolinite and iron oxide strengite in these soils indicates a low ability for protection or complexing of organic matter. Therefore, water content and microbial activity may play a more important role in the degradation of lignin and tannin, as well as the SOC stock. With the potential for future deforestation due to land use or climate change, the high lignin degradation of Gleysols indicates a vulnerability to savannah encroachment. Forest Islands isolated from the main forest biome are the most vulnerable to change, and could lose a significant proportion of their SOC stock in a transition to savannah.